ROLE OF RURAL GOVERNMENT SCHOOLS IN ACHIEVING VIKSIT BHARAT THROUGH QUALITY EDUCATION (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
India is famed for its people resources, organized society, and the world's largest democracy, which emerged from rural areas. Quality education is critical to elevating India's status from growing to viksit. This study investigates the essential role of government schools in providing high-quality education and its impact on the vision of a developed India in rural India. The study looks at the current situation of government schools in rural areas, assessing their effectiveness in providing sustainable and equitable education. The study comprised case studies, policies, reports, research articles, books, and newspapers. This study uses the qualitative method to inform policymakers and stakeholders on the critical measures required to ensure that government schools realize the aspirations of Viksit Bharat and increase educational chances for all children in rural India.